Survey and analysis of the current status of research in the field of outdoor navigation for the blind. - Lian, Yue; Liu, De-er; Ji, Wei-zhen (Disability & Rehabilitation: Assistive Technology, 2024)
In this article, we comprehensively review the current situation and research on technology related to outdoor travel for blind and visually impaired people (BVIP), given the diverse types and incomplete functionality of navigation aids for the blind. This aims to provide a reference for related research in the fields of outdoor travel for BVIP and blind navigation. We compiled articles related to blind navigation, of which a total of 227 of them are included in the search criteria. One hundred and seventy-nine articles are selected from the initial set, from a technical point of view, to elaborate on five aspects of blind navigation: system equipment, data sources, guidance algorithms, optimization of related methods, and navigation maps. The wearable form of assistive devices for the blind has the most research, followed by the handheld type of aids. The RGB data class based on vision sensor is the most common source of navigation environment information data. Object detection based on picture data is also particularly rich among navigation algorithms and associated methods, indicating that computer vision technology has become an important study content in the field of blind navigation. However, research on navigation maps is relatively less. In the study and development of assistive equipment for BVIP, there will be an emphasis on prioritizing attributes, such as lightness, portability, and efficiency. In light of the upcoming driverless era, the research focus will be on the development of visual sensors and computer vision technologies that can aid in navigation for the blind. The visual deficiency can easily help blind and visually impaired people (BVIP) to develop psychological disorders. There are few, if any, devices to meet the outdoor travel needs of BVIP in all aspects. There is no comprehensive summary and overview in the field of outdoor navigation for the blind. The selection of appropriate assistive devices can help BVIP better understand the information of their surroundings and make safer and more effective outdoor trips.